Shariah screening for compliance: a survey / Noor Latiffah Adam and Nordin Abu Bakar - Adam, Noor Latiffah; Abu Bakar, Nordi (Academy of Contemporary Islamic Studies (ACIS), 2017)
The rising awareness of Islamic values has taken shariah compliance notably into another phase of expansion in Islamic finance. One of the critical aspects in shariah compliance is screening process. Past research only outlined the screening process in general thus, screening for shariah compliance is lacking of details in the literature. This study would therefore examine the matter. The study adopts qualitative approach using expert interviews to highlight the technicalities in the screening process. The interviews outcome explains the process involved and is confirmed with the outline found from the literature. The characteristics of negative screening from the literature are also surveyed. The outcomes of the study will serve as groundwork for knowledge management as well as data analytics in Islamic finance. Once the processes and characteristics are understandable, the key points can be structured hence; it can be modeled and expanded to other area.